A HUMAN IN VITRO INVESTIGATION OF THE AUTISM SPECTRUM DISORDER RISK GENE SCN2A - Brown, Chad (My University, 2022)
Autism spectrum disorder (ASD) encompasses a group of heterogeneous disorders that affect approximately 1% of children worldwide. ASD is characterized by two core symptoms, the first being deficits in social communication and interaction, and the second being restrictive and repetitive behaviours. Although environmental and genetic factors are known to contribute to the development of ASD, the etiology remains unknown. Genetic sequencing studies have implicated over 1000 genes with risk variants that are ASD-associated. Recent sequencing studies have highlighted that SCN2A, a gene that encodes the Voltage-Gated Sodium Channel Type II Alpha Subunit habours a large proportion of genetic risk variants for ASD. An emphasis was put on this gene because many of the top genes regulate transcription and cytoskeletal dynamics and not sodium flux aiding in regulating neuron excitability. Initial investigations of complete loss of Scn2a in mice led to perinatal lethality where heterozygous loss exhibited many behavioural phenotypes associated with ASD. Through our collaboration with Dr. Stephen Scherer (Hospital for Sick Children, Toronto) we identified two de novo truncating point variants in SCN2A. In our study, we focused on using human iPSC-derived neurons for disease modelling. We found these two variants caused a reduction in synapses suggesting that neuronal communication may be altered. Furthermore, electrophysiological characterization of the neurons harbouring the differing SCN2A variants showcased that loss-of-function (LoF) variants can produce differential phenotypes based on their location. Beyond the initial ion channel characterization, we wanted to probe whether cellular pathways were altered directly or indirectly by atypical neuronal activity. Proteomics of neurons expressing the more severe variant, p.R607*, found differentially expressed proteins (DEP)s that were upregulated and downregulated. Moreover, these DEPs were enriched and clustered into cellular pathways that were altered, with one of these clusters representing mitochondrial function. We functionally validated these findings in the same neurons and found corroboration between the molecular and cellular data of impaired mitochondria. Lastly, we used Clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 gene editing to generate an isogenic model to validate our findings of the less severe p.G1744* variant. Together, this will aid in the discovery of new variant categorizations and targeted treatments for rescues of atypical neural connectivity or pathways that are altered downstream.
Keywords: Autism Spectrum Disorder; Stem cells; Neurodevelopmental Disorders; Electrophysiology; SCN2A